Taxonomy of family Benthopectinidae (Echinodermata: Asteroidea) in the Mexican waters of the Gulf of Mexico - De los Palos-Peña, Magdalena (2021)
Introduction: The family Benthopectinidae is composed of deep-sea sea stars distributed in eight genera and approximately 70 valid species. So far, only five species of this family have been reported for the Mexican waters of the Gulf of Mexico. Objective: To provide an updated local taxonomy of this family. Methods: A total of 566 specimens deposited in the Echinoderm National Collection, Instituto de Ciencias del Mar y Limnología, Universidad Nacional Autónoma de México, and the National Museum of Natural History, Smithsonian Institution, collected from 1952 to 2015, were taxonomically examined. Results: We present descriptions, photographs, and an illustrated dichotomous key for Benthopecten simplex simplex, Cheiraster (Barbadosaster) echinulatus, Cheiraster (Cheiraster) planus, Cheiraster (Christopheraster) blakei, and Cheiraster (Christopheraster) mirabilis in the region. Conclusions: The five studied species represent 6 % of the world biodiversity of the family and can now be identified with the illustrated key.